SURVEI MOTIVASI PRESTASI ATLET KLUB BULUTUNGKIS PENDOWO SEMARANG TAHUN 2014 - Kuspriyani, Dwi Sri (Universitas Negeri Semarang (Unnes), 2014)
Tujuan penelitian ini untuk memperoleh informasi atau data empiris mengenai faktor-faktor yang mempengaruhi motivasi prestasi atlet pada klub bulutangkis Pendowo Semarang Tahun 2014. Jenis penelitian ini kuantitatif. Populasinya 47 atlet-atlet klub bulutangkis Pendowo Semarang. Pengambilan sampel menggunakan teknik acak sederhana dengan sampel 36 orang. Metode pengumpulan data dengan skala likert 4 alternatif pilihan jawaban. Hasil penelitian menunjukkan 5 indikator berpengaruh terhadap motivasi atlet. Indikator faktor kepribadian, kriteria tinggi dengan persentase 78%. Indikator pengaruh situasi, kriteria sangat tinggi dengan persentase 92%. Indikator kecenderungan hasil, kriteria sangat tinggi dengan persentase 89%. Indikator reaksi emosional, kriteria sangat tinggi dengan persentase 84%. Indikator tingkah laku prestasi, kriteria sangat tinggi dengan persentase 86%. Simpulannya faktor-faktor yang mempengaruhi motivasi prestasi yaitu, faktor kepribadian, pengaruh situasi, kecenderungan hasil, reaksi emosional, dan tingkah laku prestasi. Faktor paling dominan yaitu faktor pengaruh situasi. Saran untuk pelatih, tetap memberikan program sesuai dengan target. Saran untuk atlet, janganlah cepat berpuas diri. Saran untuk orang tua atlet, senantiasa memberikan dukungan moril maupun materiil.The purposes of this research were to know what are the reasons that affect athletes motivation achievements in Pendowo Badminton Club Semarang. This research used quantitative method. The population is were 47 athletes from pendowo badminton club semarang. Sampling technique were using simple random technique with the number of samples 36. The method of data collection using likert scale with 4 alternative choices answers. The result has shown that from 5 indicators were influential to motivate athletes. Indicators are personality is at high criteria with the percentage of 78%. Indicators are influence of situation is at very high criteria with the percentage of 92%. Indicators are tendency of the result is at very high criteria with the percentage of 84%. Indicators are emotional reaction is at very high criteria with the percentage of 89%. Indicators are achievement behavior is at the very high criteria with the percentage of 86%. The conclusion of this research is the factors that influence achievement motivation is a personality factor, the influence of the situation, the tendency of the results, emotional reactions, and behavioral achievement. The most dominant factor is influence the situation factor. Suggestion for the coaches continue to monitor the athlete's performance as well as providing programs that meet the set targets. Suggestions for athletes do not quickly satisfied with the achievements that have been achieved. Advice for parents of athletes continues to provide support both morally and materially.Tujuan penelitian ini untuk memperoleh informasi atau data empiris mengenai faktor-faktor yang mempengaruhi motivasi prestasi atlet pada klub bulutangkis Pendowo Semarang Tahun 2014. Jenis penelitian ini kuantitatif. Populasinya 47 atlet-atlet klub bulutangkis Pendowo Semarang. Pengambilan sampel menggunakan teknik acak sederhana dengan sampel 36 orang. Metode pengumpulan data dengan skala likert 4 alternatif pilihan jawaban. Hasil penelitian menunjukkan 5 indikator berpengaruh terhadap motivasi atlet. Indikator faktor kepribadian, kriteria tinggi dengan persentase 78%. Indikator pengaruh situasi, kriteria sangat tinggi dengan persentase 92%. Indikator kecenderungan hasil, kriteria sangat tinggi dengan persentase 89%. Indikator reaksi emosional, kriteria sangat tinggi dengan persentase 84%. Indikator tingkah laku prestasi, kriteria sangat tinggi dengan persentase 86%. Simpulannya faktor-faktor yang mempengaruhi motivasi prestasi yaitu, faktor kepribadian, pengaruh situasi, kecenderungan hasil, reaksi emosional, dan tingkah laku prestasi. Faktor paling dominan yaitu faktor pengaruh situasi. Saran untuk pelatih, tetap memberikan program sesuai dengan target. Saran untuk atlet, janganlah cepat berpuas diri. Saran untuk orang tua atlet, senantiasa memberikan dukungan moril maupun materiil.Abstract___________________________________________________________________The purposes of this research were to know what are the reasons that affect athletes motivation achievements in Pendowo Badminton Club Semarang. This research used quantitative method. The population is were 47 athletes from pendowo badminton club semarang. Sampling technique were using simple random technique with the number of samples 36. The method of data collection using likert scale with 4 alternative choices answers. The result has shown that from 5 indicators were influential to motivate athletes. Indicators are personality is at high criteria with the percentage of 78%. Indicators are influence of situation is at very high criteria with the percentage of 92%. Indicators are tendency of the result is at very high criteria with the percentage of 84%. Indicators are emotional reaction is at very high criteria with the percentage of 89%. Indicators are achievement behavior is at the very high criteria with the percentage of 86%. The conclusion of this research is the factors that influence achievement motivation is a personality factor, the influence of the situation, the tendency of the results, emotional reactions, and behavioral achievement. The most dominant factor is influence the situation factor. Suggestion for the coaches continue to monitor the athlete's performance as well as providing programs that meet the set targets. Suggestions for athletes do not quickly satisfied with the achievements that have been achieved. Advice for parents of athletes continues to provide support both morally and materially.